Pemberian Informed Consent dalam Hal Perlindungan Hukum terhadap Tenaga Kesehatan - Gustina, Nurya; Fauziah, Faridatul; Agustina, Rani Sri (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
In era of modernity development, a critical paradigm of patients is born towards health services. Patients often have allegations that the disease that does not heal is the negligence of doctors or health workers in carrying out medical actions. This is increasingly revealed by the mass media, both electronic and print media, thus it is very important that there is approval of medical action (Informed consent) before taking action to patients and needs regulate legal protection for health workers that are clear. This can be seen in Republic of Indonesia Law Number 36 Year 2014 concerning Health Workers. In addition to Republic of Indonesia Law Number 36 Year 2014 concerning Health Workers, the granting of approval of medical actions is also an obligation that must be carried out by every health worker when going to take medical action, the things stated in Article number 1320 of the Civil Code have not fully run in accordance with the Law.